Impact of Energy Price Stabilization Mechanism on Regulated Clients’ Tariffs: The Case of Chile - Becker-Cares, C; Verdejo-Fredes, H; Garcia-Munoz, F (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The Chilean socio-political explosion in October 2019 embodies a milestone in Chile’s national history, challenging the current government’s administration and the management of state resources. One of the triggering factors of this crisis was the increase in electricity prices for those clients previously subject to flat pricing. As an example, in 2019, electricity fees increased by 25% at the national level. In order to solve the conflict, the Ministry of Energy proposed a mechanism, applicable for two years, which would freeze energy charges for companies, industries and domestic customers subject to a regulated tariff. This mechanism was employed and would produce a debt favoring generation companies, which could not exceed CLD 1.350 million. This article analyzes the effectiveness of the energy price stabilization mechanism and the effects of the Chilean socio-economic instability—resulting from the aggregated debt generated by the mechanism applicability—on the exchange rate over its duration of operation. The results suggest that the effects of the current law will not fulfill the purpose of tariff stabilization until 2024; additionally, there will be a sustained increase in tariffs until the year 2027. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.